Identity construction and maintenance in the North Atlantic c. AD800-1250 - Knight, Dayanna (2014)
This study is a multivalent investigation of Scandinavian identity formation and cultural structures within the north Atlantic that looks specifically at the construction and maintenance of island identities circa AD800-1250. This not only includes consideration of the Norse settlers but also the effects of contact between the emerging island cultural identities and continental Europe. In order to do this zones of settlement have been defined to better compare the expansion of medieval Scandinavian populations in terms of microscale practices and interactions within family groups and the macroscale vectors of social, economic and political change. It employs a wide variety of material that makes use of aspects of both prehistoric and historic sources. The variety of enabling conditions ultimately provided for a time the circumstances necessary for the long-term success of a number of the settlements established during this period. The evidence is considered in as subjective manner as possible with the sources available also reflecting the conditions of initial region excavation and publication.